Comparative analysis of sustainable logistics between the Port of Veracruz in Mexico and the Port of Cartagena de Indias - Boyano-Fram, Teofilo Omar; Hernández-Cobo, Juan Sebastián (EFIM Ediciones, 2018)
Trade is the main economic activity that marks out the economic development of nations, it is therefore very important the analysis of the capacities of the ports, because they are largely responsible for such activity goes beyond the borders of nations. The objective of this document is to carry out a com-parative analysis that allows to understand the importance of the ports of Veracruz in Mexico and Cartagena in Colombia in terms of logistics and sustainable development. Some of the findings show that, although the morphological conditions give greater advantage to the port of Veracruz, the port of Car-tagena has strong strategic alliances, which improves itself for the execution of logistical maneuvers.